(untitled) (Bulletin of Innovative Research, 2026)
The article examines figurative schemes underlying the representation of the concept of “beauty” in the linguistic worldview. The study is grounded in cognitive linguistics and linguocultural analysis. The introduction substantiates the relevance of investigating conceptual structures as mediators between language and culture. The literature review outlines major theoretical approaches to conceptual metaphor, image schemas, and cultural semantics. The methodological section describes a comparative analysis of lexical, phraseological, and metaphorical realizations of the concept in different linguistic traditions. The results demonstrate that the conceptualization of beauty relies on universal embodied image schemas (light, harmony, integrity, elevation) while simultaneously revealing culturally specific symbolic associations. The conclusions summarize the interaction between universal cognitive mechanisms and culture-bound semantic models in shaping the linguistic representation of beauty.